TEACHER SELF EFFICACY IN NATIONAL SECONDARY SCHOOLS AT PENINSULAR MALAYSIA - Liang, Fei Shin; Tai, Mei Kin (International Journal of Education, Psychology and Counseling, 2021)
Teacher self-efficacy is a cognitive process that allows an individual to measure the level of self-confidence in behavior change. In relation to that, this study was conducted to identify the level of self-efficacy of teachers in National Secondary School (SMK) in Peninsular Malaysia. Three dimensions namely Student Engagement, Instructional Strategies, and Classroom Management were measure in this study. There were 357 teachers selected randomly for this study. Data were collected through a questionnaire using the Teacher Sense of Efficacy Scale (TSES) instrument. Data were analyzed using descriptive statistics to describe the level of self-efficacy of teachers. The findings of the study show that the level of self-efficacy of teachers in SMK in Peninsular Malaysia at a high level (Mean = 4.15, SP = .425). Student Engagement dimension (Min = 4.11, SP = .443), Instructional Strategies dimensions (Mean = 4.15, SP = .456) and Classroom Management dimension (Mean = 4.19, SP = .491).